Preferential Habitat of Orange Footed Scrubfowl (Megapodius reindwardt) at Nature Tourism Park of Mount Tunak, Lombok Tengah Regency, Nusa Tenggara Barat Province - Oktovianus Oktovianus; Harnios Aerief; Agus Hikmat; Jarwadi B. Hernowo; Rachmad Hermawan (Media Konservasi, 2018)
Orange Footed Scrubfowl (Megapodius reindwart Dumont 1823) is classified as protected bird based on the Preservation of Plant and Animal Species of  Ministry of Enviromental and Forestry Decree No. 92/2018. As a natural park, TWA of Gunung Tunak serves as a natural conservation area (NCA) which has a basic function as a conservation area designated as a recreation area and nature tourism. Associated with its function then TWA of Gunung Tunak has an important role in supporting the conservation of wild animals especially Orange Footed Scrubfowl and the implementation of recreational activities and natural tourism in a sustainable manner. The objectives of this study were to analysis the preferential habitats of Orange Footed Scrubfowl. Based on the results of multiple linear regression analysis of stepwise method, it can be known that dominant factors to the frequency of presence of Orange Footed Scrubfowl in a selected habitat are the number of predators, the distance from water source, soil texture, and altitude of place with the equation Y = 3.390.96 + 2.28X11 + 0.00084X5 - 0.0117X10 - 0.0034X3. Based on the results of preference index analysis with Neu method, it can be seen that the preferred area of Orange Footed Scrubfowl is only in Block I (w ≥ 1) namely the forest area near Teluk Ujung Coast. Based on the place altitude, the existence of the mound of nest from the sea surface, the Orange Footed Scrubfowl prefer the area at an altitude of 0-25 m above sea level. Keywords: Megapodius reindwart, Nature Tourism Park of Mount Tunak, orange footed scrubfowl, preferential habitat